Evidence Brief: Strengthening Public and Patient Engagement in Health Technology Assessment in Ontario - Gauvin, François-Pierre; Abelson, Julia; Lavis, JN (My University, 2014)
An assessment of what is known about problems related to health technology assessment, options for addressing these problems, and key implementation considerations. The evidence brief was an input to a stakeholder dialogue on the topic of strengthening public and patient engagement in health technology assessment in Ontario.
Keywords: public; patient; health technology assessment; Ontario